1994
DOI: 10.1139/z94-232
|View full text |Cite
|
Sign up to set email alerts
|

Winter habitat use by mule deer in the central interior of British Columbia

Abstract: We analyzed winter habitat use by 23 radio-collared mule deer (Odocoileus hemionus hemionus) in the central interior of British Columbia, Canada, from February 1982 to March 1989. This research was essential to provide sound biological data for development of a selection silvicultural and planning system that would integrate timber harvesting with the habitat needs of mule deer. Habitat selection was analyzed by comparing deer use with habitat availability of various levels (categories) of the following variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 14 publications
5
40
0
2
Order By: Relevance
“…This is in agreement with previous studies (Armleder et al 1994;Poole and Mowat 2005) that found that in late winter, Mule Deer seek late-successional coniferous stands with greater crown closure. This study also showed that, in 2006, a large number of Mule Deer tracks were located in Douglas-fir-leading stands, as it was found in west-central (D'Arcy and Stark 1998*) and south-central (Armleder et al 1994) interior regions rich in Douglas-fir stands. In this study, however, the distribution of Douglas-fir stands was patchy, and Mule Deer also used Lodgepole Pine-Hybrid White Spruce stands that provided animals with canopy cover.…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with previous studies (Armleder et al 1994;Poole and Mowat 2005) that found that in late winter, Mule Deer seek late-successional coniferous stands with greater crown closure. This study also showed that, in 2006, a large number of Mule Deer tracks were located in Douglas-fir-leading stands, as it was found in west-central (D'Arcy and Stark 1998*) and south-central (Armleder et al 1994) interior regions rich in Douglas-fir stands. In this study, however, the distribution of Douglas-fir stands was patchy, and Mule Deer also used Lodgepole Pine-Hybrid White Spruce stands that provided animals with canopy cover.…”
Section: Discussionsupporting
confidence: 94%
“…Animals preferred higher canopy cover when it was cold compared to average temperatures or when snow heights of our reference weather station exceeded 60 cm. This result is consistent with previous studies on ungulates in general [41][42][43][44], and roe deer in particular [45,46]; these studies also observed a preference for higher canopy cover at low temperatures and in deep snow. The result confirms our expectations that roe deer use forests with high canopy cover as thermal shelter when temperatures are low.…”
Section: Discussionsupporting
confidence: 93%
“…Habitat use by this species is particularly important during winter periods when this ungulate seems to require latesuccessional closed canopy forests to provide snow interception and forage from herbs, shrubs and litterfall of arboreal lichens and Douglas-fir (Dawson et al, 1990;Nyberg, 1990;Armleder et al, 1994). To date, investigation of relative habitat use by mule deer during summer and winter seasons in those sites harvested by various retention schemes has received little attention.…”
Section: Introductionmentioning
confidence: 99%